An Evaluation of the Effectiveness of Namibian Banks’ Competitive Strategies in Response to Technological Advancements: A Case Study - Simasiku, Priscilla; Semente, Efigenia Madalena Mario (Journal of Business and Strategic Management, 2025)
Purpose: The Namibian banking industry faces serious competition, making competitive strategy design a critical agenda. The banks must adjust their banking models, and strategies and align them to technological advancements in the industry. This study explores the impact of technology on the banking industry using Porter’s Five Forces model. The five forces are customers' bargaining power, suppliers' availability of substitute products, rivalry in the industry, and new entrants in the industry. The study examined how advancing technologies influence competition and employee performance, particularly when the model is applied effectively. Methodology: Using a quantitative, descriptive explanatory approach, data was collected via a 5-point Likert scale questionnaire from 269 randomly selected respondents, spanning various hierarchical levels. The data was analysed using SPSS and the results were presented in the form of frequencies percentages and tables and figures. Findings: The study found that banks in Namibia have a stronger link between technology and the bargaining power of customers and a weaker relationship between technology and the bargaining power of suppliers. The study further found a likely awareness of technological usage by the bank's staff resulting in a demand for upskilling in digital banking solutions. Unique contribution to theory, practice and policy: The study concluded that while Porter's Five Forces model remains relevant, its application must adapt to technological advancements to sustain competitive performance. Recommendations include training programs, strategic refinements, and proactive measures to mitigate competitive threats.